2014
DOI: 10.1287/opre.2014.1256
|View full text |Cite
|
Sign up to set email alerts
|

Assortment Optimization Under Variants of the Nested Logit Model

Abstract: We study a class of assortment optimization problems where customers choose among the offered products according to the nested logit model. There is a fixed revenue associated with each product. The objective is to find an assortment of products to offer so as to maximize the expected revenue per customer. We show that the problem is polynomially solvable when the nest dissimilarity parameters of the choice model are less than one and the customers always make a purchase within the selected nest. Relaxing eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
165
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(169 citation statements)
references
References 30 publications
3
165
0
1
Order By: Relevance
“…As a shortcoming, this added complexity results in more complex optimization problems. For example, Davis et al [14] have shown that the optimization of the Nested logit model is in general a NP-hard problem.…”
Section: Related Workmentioning
confidence: 99%
“…As a shortcoming, this added complexity results in more complex optimization problems. For example, Davis et al [14] have shown that the optimization of the Nested logit model is in general a NP-hard problem.…”
Section: Related Workmentioning
confidence: 99%
“…The variants of the assortment optimization problems they study include the introduction of cardinality constraints, the concept of display location based attractiveness, the integration of the pricing decision from a list of possible price levels, the quality consistent pricing and the concept of product precedence constraints. Davis et al (2013b) study the assortment optimization problem, without any constraints on the products, under a nested logit model, where customers first choose a nest of products and then a product from the nest. They identify special cases where the problem is polynomially solvable and they develop tractable methods to obtain the assortments for the NP-hard cases of the problem.…”
Section: Related Literaturementioning
confidence: 99%
“…From the point of view of mathematics, when given a data matrix, to optimize the terrain is network by minimizing the following objective function [32][33][34][35].…”
Section: Mathematical Optimization For Image Processing Tasksmentioning
confidence: 99%